De la pleine terre sous le terre-plein : géomorphologie du polder de la rive droite de Bordeaux - TVK; Pierre Alain Trévelo; Antoine Viger-Kohler; David Malaud; Phoebe Eddleston; Amandine Nana (Projets de Paysage)
Over the last twenty years, the topsoil has reappeared on the former industrial sites on the right bank of the River Garonne in the city of Bordeaux. After a period of neglect, several major projects have helped to build the structural framework of a landscape in the residential development of this vast polder which was built from the 18th century onwards. Re-exposing the topsoil has provided an opportunity to reintroduce water into the landscape by creating spaces that can be flooded if the river breaches the embankment. These types of projects which are now for the most part developed within a context of limiting urban sprawl require an in-depth geomorphological understanding of the landscape. By tracing the geo-formation of the polder on the right bank of the river Garonne, the article places contemporary projects within the historical context of this piece of land. It invites us to redefine infrastructures no longer as systems for controlling and conquering land but as systems of mediation with the soil’s biogeochemical phenomena.